Methods Of Treatment Of Inflammation Related Conditions Using Pluripotent Anti-inflammatory And Metabolic Modulators - Segovia, Mercedes; Escande, Carlos; Capuccio, Rosina Dapueto; López, Gloria Virginia; Hill, Marcelo; Porcal Quinta, Williams Arturo; Duarte, Jorge Rodriguez; Galliussi López, Germán Adrian; Batthyány, Carlos; Garat Nuñez, Maria Pia (2022)
Methods of treating acute and chronic inflammatory conditions, tissue transplant rejection, and/or organ transplant rejection comprising administering to a subject in need thereof a therapeutically effective amount of a pluripotent anti-inflammatory and metabolic modulators optionally in combination with one or more secondary therapeutic agents and pharmaceutical compositions thereof.